Predictors of Sexual Orientation Diversity in Intercollegiate Athletics Departments - George B. Cunningham (University of Kansas Libraries, 2010)
In adopting a multilevel perspective, the purpose of this study was to examine antecedents of sexual orientation diversity among university athletic departments. Data were gathered from top administrators (N = 653) in 199 athletic departments. Hierarchical regression analysis indicated that the size of the university, the racial diversity of department employees, and the gender diversity of department employees were all positively associated with sexual orientation diversity. The entire model explained 24% of the variance. The author discusses ways to increase sexual orientation diversity, study contributions, limitations, and future directions.